2019
DOI: 10.1371/journal.pone.0212674
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism behind lack-of-effect of lanthanum on seed germination of switchgrass

Abstract: Switchgrass ( Panicum virgatum L.) is a perennial warm-season C 4 grass identified as a model species for bioenergy feedstock production. Lanthanum (La) as a rare earth element can stimulate the physiological processes of plant growth. The purpose of this study was to investigate the effect of lanthanum on seed germination of switchgrass. However, no significant differences in seed germination were found. The energy dispersive X-ray analysis showed that abundant la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
0
1
Order By: Relevance
“…Several studies have investigated the seed germination of switchgrass under La or ABA stress. Thomas et al [31] found that La had no effect on germination of switchgrass at any dose, which was consistent with our previous work [32]. Duclos et al [18] showed that ABA inhibited the germination of switchgrass at a dose equal to or larger than 10 μM.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Several studies have investigated the seed germination of switchgrass under La or ABA stress. Thomas et al [31] found that La had no effect on germination of switchgrass at any dose, which was consistent with our previous work [32]. Duclos et al [18] showed that ABA inhibited the germination of switchgrass at a dose equal to or larger than 10 μM.…”
Section: Introductionsupporting
confidence: 81%
“…In the present study, we observed that La and ABA had no significant effect on seed germination, suggesting that the caryopsis covering structure was somewhat restrictive to the movement of macromolecular substances [32], and that ABA could significantly promote the root growth of switchgrass, while La could not alleviate the promotion of root growth by ABA. The root is the major organ for the absorption of water and nutrients.…”
Section: Discussioncontrasting
confidence: 51%